A geração de valor por meio da aplicação do marketing em pequenas empresas: um estudo na área médica - Rosa, Ana Teresa Ratti de Oliveira (2013)
Due to the increasingly competitive among small medical companies and the expectations of customers in this market, this study aims to discuss ways of marketing being a value generator for small companies providing medical services. Thus, we developed a case study of the Pediatric Clinic and Vaccinations Dr. Paul Rose Ltda. At this company was made the application of the philosophy of strategic management and guided by the fundamentals of marketing which resulted in significant expansion of the offer value to the public and consequently a higher potential for profitability and market share of the Taubaté City the São Paulo State, which has 603 health facilities, and of these, 384 are isolated clinics and 124 are clinics and specialization centers. For this qualitative research, with a unique case of study, the triangulation of data was made through in-depth interviews with workforce (managers and employees),with external public (costumers) and documentary survey (database of the company and external). The theoretical foundation in marketing as value generator was essentially guided by concepts which call for building business value through the provision of differentials that are grounded in the needs of the market and consider the corporate capacity. Were adopted, too, concepts and authors who value building lasting relationships between companies and their customers. The main results are related to the possibilities of differentiation of small business in the medical field through the application of marketing. The main findings of this study indicate that the consequences of the application of marketing are financial, market positioning, brand building, development of personal skills and, especially, the value perception of the final customer